Pengeringan Bengkuang Menggunakan Freeze Vacuum Drying Dengan Kapasitas 1 Kg - Dhewaji, Roe Dwi; Martin, Awaludin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Freeze vacuum drying is one of the best drying methods for preserving foodstuffs. Besides being one of the solutions for post-harvest technology, freeze vacuum drying is also able to increase the selling value of an ingredient. This research is a follow-up study of freeze vacuum drying where in previous studies it was found that the maximum water loss is 78% of the mass of 50 g yam with the drying chamber temperature kept at -9ºC within 4 hours, using a quick-drying method that utilizes heat from the condenser for secondary drying. In this case, the condenser will be cooled using water, the heat from condenser will be discharged and will be absorbed by water, the water will be flowed into the drying chamber, with the temperature of the water flowing at 40ºC. This study aims to develop a freeze vacuum drying method using self-heating system by utilizing heat condenser. The maximum water loss in this study was 77.2% of 1 kg mass at a constant temperature of -6ºC for 4 hours, with the energy consumption used 4.73 kWh. Keyword: Freeze, Vacuum, Drying, Yam.